Study on the preparation and performance comparison of side-chain hydroxyl-terminated polybutadiene derivatives with narrowly molecular weight distribution used for polyurethane. (December 2021) - Ma, Lingxiao; Zhu, Xiuzhong; Zhang, Wanbin; Zhang, Haitao; Wang, Jianyong; Qu, Jianbo
Abstract: Hydroxy-terminated oligomers with narrow molecular weight distribution using as soft segment of polyurethane can significantly increase the modulus, tensile strength, and elongation at break of the polyurethane. Thus, design and synthesis of new hydroxy-terminated oligomers having narrow molecular weight distribution can improve the properties of polyurethane and further expand the use range of polyurethane. A set of side-chain hydroxyl-terminated polybutadiene (HTPB) derivatives were successfully synthesized by anionic polymerization and blue light photocatalytic thiol-ene reaction. Firstly, HTPB with narrow molecular weight distribution was synthesized via anionic polymerization using mono-lithium based initiator and followed by de-protection. Then, HTPB derivatives with different side-chains such as butyl, ethyl acetate, or myristyl, namely HTPBbut, HTPB eac and HTPBtet, were obtained by blue light photocatalytic thiol-ene reaction using Ru(bpy)3 Cl2 as photoredox catalyst and HTPB as matrix polymer. Similar with HTPB, those HTPB derivatives also have narrow molecular weight distribution. Polyurethane elastomers (PUs) were synthesized with HTPB or HTPB derivatives as soft segment, toluene diisocynate (TDI) as hard segment, and 1, 4-butanediol as chain extender. Compared study the performances of polymers, the results showed that glass transition temperature ( T g ) and viscosity of HTPB derivatives were increased when short-chain side groups were introduced. But instead, T g and viscosity of HTPB derivatives was reduced following long-chain side groups being grafted. Through comparing research of properties for PUs, tensile strength is reduced and elongation at break is augmented, when side groups were introduced in HTPB backbone. Research on the contact angle tests of PUs indicated that the contact angle of PUs using HTPB, HTPBbut or HTPBeac as soft segment, is similar, and PUs using HTPBtet as soft segment has a larger contact angle about 137.2 °C. Highlights: A set of side-chain hydroxyl-terminated polybutadiene (HTPB) derivatives with narrow molecular weight distribution were successfully synthesized. The HTPB derivatives with different pendant groups have distinct differences in glass transition temperature and viscosity. Polyurethane elastomers using HTPB derivatives as soft segment have distinct differences in breaking strength, elongationand the contact angle.